Vection Induced by Illusory Motion in a Stationary Image. (September 2013) - Seno, Takeharu; Kitaoka, Akiyoshi; Palmisano, Stephen
Ilusory self-motion (vection) can be induced by large areas of visual motion stimulation. Here we demonstrate for the first time that illusory expansion can induce vection in the absence of any physical display motion.